Cobalt(III) as a stable and inert mediator ion between NTA and His6-tagged proteins - Wegner, Seraphine V.; Spatz, Joachim P. (Angewandte Chemie. International edition, 2013)
The Co3+-mediated interaction between nitrilotriacetic acid (NTA) and the His6-tag is so stable and inert towards ligand exchange that it has a half-life of 7 days in the presence of imidazole and survives even under strongly chelating as well as reducing conditions, unlike the commonly used Ni2+ or Co2+ complexes. Possible applications include the separation of labeled proteins and the stable immobilization of proteins on surfaces.